Enhancement of α-Mangostin Wound Healing Ability by Complexation with 2-Hydroxypropyl-β-Cyclodextrin in Hydrogel Formulation - Wathoni, Nasrul (Pharmaceuticals (Basel), 2020)
α-Mangostin (α-M), one of the active compounds in Garcinia mangostana peel, has been effectively used in wound healing. However, its poor solubility in aqueous solution causes low bioavailability for skin ulcers, hindering its application in wound healing. The aim of this study was to improve the solubility of α-M through complex formation with 2-hydroxypropyl-β-cyclodextrin (α-M/HP-β-CD CX) and to evaluate the healing activity of the complex. The α-M/HP-β-CD CX was incorporated in a sodium carboxymethylcellulose hydrogel (α-M/HP-β-CD CX HG), and the in vivo healing activity was examined in mice. Evaluation of α-M/HP-β-CD CX HG, including organoleptic evaluation, homogeneity, pH, spreadability, swelling ratio, consistency, scanning electron microscopy (SEM), and in vitro drug release, was carried out. The complex formation of α-M/HP-β-CD CX was confirmed by FTIR and PXRD analysis. The solubility of the α-M/HP-β-CD CX in water linearly increased about 11.7-fold compared to α-M alone, and by 3.5-fold compared to the α-M/HP-β-CD physical mixture (α-M/HP-β-CD CX PM). The α-M/HP-β-CD CX HG was homogenous, the pH was found to be in the neutral range, the spread area was 5 cm, and the consistency was stable until 14 days. SEM analysis showed that α-M/HP-β-CD CX HG surged due to the porous structure of the HG. In addition, in vitro release of α-M from α-M/HP-β-CD CX HG was considerably increased compared to α-M/HP-β-CD PM HG and α-M HG. Notably, in vivo evaluation in mice showed that α-M/HP-β-CD CX HG significantly accelerated the wound healing ability compared to other HGs. Thus, α-M/HP-β-CD CX HG has potential as a new formulation of α-M for wound healing therapy.